ANALYSE DE LA PERFORMANCE FINANCIERE DE LA SOCIETE « PLANTATIONS ET HUILERIES DU CONGO » (PHC) de 2003 à 2007 - Pierre, LOMATA MELENGE Jean-; NGUTU BASEKAWIKE Philomène (IJRDO - Journal of Business Management, 2021)
Our research focused on the analysis of the financial performance of the former company "Plantations et Huileries du Congo", PHC in acronym, for a period of five years, from 2003 to 2007. Our objective is to verify whether the financial health of the Company PHC was healthy five years after the two wars of liberation and to identify the underlying reasons that led our company under study to sell all its plants and abandon palm oil production. Through the financial analysis of PHC’s financial statements from 2003 to 2007, an analysis conducted in two forms including arithmetic analysis of balance sheet items and the use of ratios, we confirmed our hypothesis that PHC experienced financial underperformance five years after the two wars in Congo. The company experienced a financial imbalance and its invested capital was not profitable. This is the fundamental reason why in September 2009 the Unilever Group decided to give up palm oil production and to sell all its plants and plantations to a subsidiary (Feronia) of the Canadian company Trinorth